Ask a question

how can I find the GCF for a^3b-ab^3

How do I find the Greatest Common Fcator for the list of terms:


1 Answer by Expert Tutors

Tutors, sign in to answer this question.
Jonathan A. | Physics PhD - Math and Physics tutoringPhysics PhD - Math and Physics tutoring

There is some ambuguity to what you wrote, but based on the context I think this is what you mean:

(a^3)*b - a*(b^3)

Notice that both terms have one 'a' and one 'b'. We can rewrite this as:

(a^3)*b - a*(b^3) = (a^2)*ab - (b^2)*ab = a*b*(a^2 - b^2)

[since a^3 = a*a*a = a*(a^2) = (a^2)*a]

So 'ab' is the GCF.